Pengaruh Kinerja Driver Terhadap Pendapatan Dengan Variabel Usia Sebagai Moderasi - Imam Fahruddin; Misbahul Munir; Indah Yuliana (Jurnal Ilmu Ekonomi, 2023)
The purpose of this study was to determine the effect of performance on income and the role of age in moderating the effect of performance on income. This research was carried out using the MRA (Moderate Regression Variable) approach with a sample of 150 respondents from the entire motorcycle taxi population in Malang. After confirming the validity of the questionnaire data and the classical assumption test, the results of this study can be explained as follows. First, performance has a positive and significant effect on income, meaning that the higher the performance of the drivers, the income of the drivers will increase. Both ages play a role in moderating the performance of the drivers to increase revenue. In the sense that age plays a role in strengthening the influence of the performance of drivers on income.